La creación del derecho en las decisiones de la Corte Constitucional Italiana - Miranda Bonilla, Haideer (2026)
This study analyzes the creative role of Law, particularly, in the procedural field that the Italian Constitutional Court has had by developing, via jurisprudence, a wide typology of sentences on the control of constitutionality of the norms, beyond the traditional classification of conviction and acquittal judgments. This has been a reference, since it has been used by other constitutional jurisdictions.